PROTOPLAST ELECTROFUSION FOR DEVELOPMENT OF SOMATIC HYBRIDS BETWEEN PLEUROTUS FLORIDA AND PLEUROTUS SAJOR-CAJU - LOVELEEN KAUR; S. KAPOOR (International Journal of Pharma and Bio Sciences, 2014)
Interspecific hybrids of Pleurotus florida PF-5 (MTCC 1801) and Pleurotus sajor-caju PSC-3 (ATCC 62887) were developed using electrofusion. A concentration of 2mM vanillin and 1000ppm carbendazim were selected as screening markers for the hybrids of the two Pleurotus spp. The electrofusion using an exponential decay was best with 1000 V (2 pulses with an interval of 5 sec). With square wave discharge, maximum regenerants were obtained with 2 pulses at a pulse voltage of 300V at an interval of 30 seconds. Maximum regeneration efficiency was 14.2 per cent on generation Minimal Medium. 11 hybrids were selected and characterized on the basis of morphological and biochemical characters. Isozyme analysis and molecular characterization of hybrids along with the parents using RAPD-PCR suggested that the fusants obtained were hybrids with both parental and non-parental characters. Cropping trials of the hybrids showed that the spawn run period varied from 19 days (PFPS-131) to 42 days (PSPF-95). Two hybrids, PSPF-47 and PSPF-101 were found to give significantly higher yield (88.8% and 82.2%, respectively) than the parent strains while two hybrids, PFPS-54 and PFPS-168 gave considerably lower spore mass and lower spore count as compared to parent strains.